A General Route to Flame Aerosol Synthesis and In Situ Functionalization of Mesoporous Silica. Issue 35 (21st July 2022) - Liu, Shuo; Dun, Chaochao; Chen, Junjie; Rao, Satyarit; Shah, Mihir; Wei, Jilun; Chen, Kaiwen; Xuan, Zhengxi; Kyriakidou, Eleni A.; Urban, Jeffrey J.; Swihart, Mark T.
Abstract: Mesoporous silica is a versatile material for energy, environmental, and medical applications. Here, for the first time, we report a flame aerosol synthesis method for a class of mesoporous silica with hollow structure and specific surface area exceeding 1000 m 2 g −1 . We show its superior performance in water purification, as a drug carrier, and in thermal insulation. Moreover, we propose a general route to produce mesoporous nanoshell‐supported nanocatalysts by in situ decoration with active nanoclusters, including noble metal (Pt/SiO2 ), transition metal (Ni/SiO2 ), metal oxide (CrO3 /SiO2 ), and alumina support (Co/Al2 O3 ). As a prototypical application, we perform dry reforming of methane using Ni/SiO2, achieving constant 97 % CH4 and CO2 conversions for more than 200 hours, dramatically outperforming an MCM‐41 supported Ni catalyst. This work provides a scalable strategy to produce mesoporous nanoshells and proposes an in situ functionalization mechanism to design and produce flexible catalysts for many reactions. Abstract : A continuous flame aerosol route to synthesize hollow structured mesoporous silica nanoparticles is presented, and a general in situ functionalization mechanism for loading highly dispersed catalytically active sites is proposed. Multiple applications are addressed in this class of material, including heterogeneous catalysis, dye adsorption, drug delivery, and thermal insulation.